SAT0480 High Doses of Infliximab in the Management of Juvenile Idiopathic Arthritis. (23rd January 2014) - Cron, R. Q.; Tramballi, A.; Beukelman, T.; Weiser, P.; Atkinson, T. P.; Stoll, M. L.
Abstract : Background: Although biologics have revolutionized treatment of juvenile idiopathic arthritis (JIA), many patients have active disease despite therapy [1 ]. Studies have shown benefit of dose intensification of infliximab in several conditions, including inflammatory bowel disease, psoriasis, and idiopathic uveitis [2, 3 ]. However, the safety and effectiveness of infliximab dose intensification have not been evaluated in JIA. Objectives: We routinely use high doses of infliximab (10–20 mg/kg/dose) in children with recalcitrant JIA or complications thereof. The objective of this study was to review our experiences with high-dose infliximab in JIA. Methods: We performed a retrospective review of children with JIA who received infliximab at ≥10 mg/kg/dose. We recorded all serious adverse events (SAE), medically important infections, and infusion reactions. We also recorded the ESR, physician global assessment of disease activity (MD global), and active joint count (AJC) at initiation of high dose infliximab and 3, 6, and 12 months thereafter. Institutional Review Board approval was obtained from the University of Alabama at Birmingham for this study. Results: 75 subjects received a total of 1, 367 infusions over 126.8 person-years. There were a total of 11 SAEs (8.7 / 100 person-years), seven of which were potentially related to therapy; and 10 infusion reactions (0.7%), two constituting anaphylaxis. Statistically significant improvements were observed in the AJC (median 0 [range 0 – 31] versus 2 [0 – 39]) and MD global (12 [0 – 31] versus 21 [0 – 80]) assessments of disease activity over the first year. Conclusions: High dose infliximab resulted in improvements in markers of JIA disease activity. The incidence of SAEs with high dose infliximab was similar to that reported in long-term outcome of a randomized clinical trial of standard dose infliximab for JIA [4 ], and the incidence of infusion reactions was even lower. High dose infliximab appears safe and effective in the management of JIA. Future studies are necessary to compare prospectively dose intensification with alternative therapeutic options. References: Shenoi S, Wallace CA. Paediatr Drugs. 2010;12:367. Kahn P, et al. Ophthalmology. 2006;113:860. Reguiero M, et al. Inflamm Bowel Dis. 2007;13:1093. Ruperto N, et al. Ann Rheum Dis. 2010;69:718. Acknowledgements: We thank the patients and families for agreeing to dose amplification of infliximab in medically refractory disease. Disclosure of Interest: None Declared